THE PENAMBAHAN CONTRACT RELAX STRETCHING PADA INTERVENSI IFC DAN ULTRASONIK DAPAT MENGURANGI NYERI LEBIH BAIK PADA SINDROMA MIOFASIAL OTOT SUPRASPINATUS - Faizah, Zuriatun (Majalah Ilmiah Fisioterapi Indonesia, 2013)
This study aims to determine the effect of the addition of Contract Relax Stretching on IFC’s and Ultrasonic’s interventions for reduce of pain on myofascial syndrome of supraspinatus muscle. The samples obtained at Indra Hospital of Bali Province, conducted in May-August 2011. With a sample of 20 people both men and women, ages 44-59 years sampled. The number of samples divided into 2 groups: a control group of 10 people with IFC and Ultrasonic intervention and 10 treatment groups with the IFC, Ultrasound and Contract Relax stretching. Supraspinatus muscle miofasial syndrome is a condition characterized by an hypersensitive region called the trigger area in the muscle or loose connective tissue in the shoulder which, together with the presence of a specific inflammatory response in areas related to the trigger point when the trigger area is given a stimulation. This condition is obtained by purposive sampling in accordance with existing assessment table. The reason for the existence of macro trauma and poor posture microns. Data processing and statistical analysis using the Program for Social Science (SPSS). Ultrasonic IFC and have a therapeutic effect is a reduction in pain. Wilcoxon test results in the control group with a P value of 0.012 (p <0.05), which means there is a significant effect on pain reduction. Based on the reduction of the graph looks more sharp pain treatment group compared with the control group. Obtained from Mann Whitney test p 0.007, which means there is a very significant effect of adding the group treated with the control group. Thus the application of IFC, Ultrasound and Contract Relax stretching is very effective and optimal conditions can nmengurangi pain syndrome miofasial supraspinatus muscle.
Keywords: Supraspinatus Miofascial Syndrome, VAS, Contract Relax Stretching.